Problem aspects regarding the establishment of territory boundaries of territorial communities (in the current times and in the post-war period) - Dorosh, Y.; Tarnopolskyi, А.; Kharytonenko, R.; Derkulskyi, R.; Riabova, Y. (Land Management, Cadastre and Land Monitoring, 2022)
It is emphasized that the issue of establishing the boundaries of the territories of territorial communities currently remains relevant in Ukraine and presents new challenges caused by the state of war. The sequence (stages) of land management works related to establishing the boundaries of the territories of territorial communities is proposed. It is assumed that in the post-war period, the boundaries of the territories of territorial communities may be limited in their establishment, if these boundaries were located in the area of military (combat) operations or were under temporary occupation, encirclement (blockade). Attention is focused on the difficulties associated with the financial capacity of territorial communities in ordering work on the development of land management projects to establish the boundaries of these communities in the event of a return to peaceful life. The existence of disputes regarding the common borders between certain adjacent territorial communities made it necessary to introduce the possibility of partially establishing the borders of the territories of territorial communities in relation to crossing the border.Ways of improving the process of establishing the boundaries of the territories of territorial communities and adapting it to the conditions of the state of war and the post-war period are proposed, through the examples of post-war boundary establishment in foreign countries. Proposals will be made regarding amendments to the land legislation related to the definition of the boundaries of the territories of territorial communities as a whole, as well as individual parts thereof.Keywords: administrative-territorial unit, boundary of the territory of the territorial community, State land cadastre, land management